Estimating New Zealand's Structural Budget Balance - Oscar Parkyn (New Zealand Government, The Treasury, 2010)
Existing methodologies for estimating a government's structural budget balance are reviewed and applied to the case of New Zealand. Besides the conventional cyclical adjustment, an assessment is made of other possible non-structural elements to the budgetary position, including the terms of trade, asset prices and unbalanced growth. A key result is that the terms-of-trade boom, which began in the late 2000s, is associated with around 1% of GDP in tax revenues that may not be structural. Uncertainty surrounding cyclically-adjusted balance estimates is presented using fan charts.
Keywords: E62; H62; 330; fiscal policy; business cycle; terms of trade; asset prices; Haushaltsdefizit; Finanzpolitik; Konjunktur; Terms of Trade; Neuseeland